Clinical Evaluation of Wear Behavior of Human Enamel and Chipping of Veneered Zirconia against Monolithic Zirconia (Randomized Controlled Clinical Trial) - Ibrahim, Nouran Mahmoud; El-basty, Reham; Katamish, Hesham (Brazilian Dental Science, 2020)
Objective: To evaluate the wear behavior of human enamel and chipping of veneered and monolithic zirconia for posterior full coverage restorations. Material and methods: Thirty-four zirconia full coverage restorations (seventeen in each group) were fabricated. The patients were divided into two groups according to the type of zirconia used; group 1 (comparator group) veneered zirconia crowns and group 2 (intervention group) monolithic zirconia single crowns. All crowns were lab fabricated and polished. For opposing teeth wear measurements 3D non-contact profilometer was used where epoxy resin replicas were constructed for opposing arch immediately after crowns cementation, three, six and twelve months. Restoration chipping was measured using modified United States Public Health Services (USPHS) criteria. Results: All restorations were reported as alpha with no chipping. There was no statistically significant difference between (Group 1) and (Group 2) for wear test. Conclusion: Both monolithic and veneered restorations revealed satisfactory mechanical properties with no chipping after one year of clinical use. Wear of opposing enamel was clinically acceptable for both materials.KeywordsCeramics; Chipping; Monolithic zirconia; Veneered zirconia; Wear.